To solve the equation \(3x + 5y = 60\) for \(y\), follow these steps:
-
Subtract \(3x\) from both sides of the equation: \[ 5y = 60 - 3x \]
-
Divide both sides by \(5\): \[ y = \frac{60 - 3x}{5} \]
-
Simplifying that expression: \[ y = \frac{60}{5} - \frac{3x}{5} = 12 - \frac{3}{5}x \]
Thus, the correct effect does result in the equation \(y = 12 - \frac{3}{5}x\), but from the given choices, the option that matches with this is:
- \(y = 60 - 3x\), since dividing the entire equation (including the 60) by 5 results in a different expression.
None of the provided options are exactly in the standard solved form. But note that the rewritten format of our solution will depend on how the mathematics hold out when applied to each variable involved.
If we focus specifically on what is expressed:
- The closest appropriate response reflecting the rearranged components is \(y = \frac{60 - 3x}{5}\), which simplifies notions to isolate component variables originating from the opened brackets.
So, based on the original equation \(3x + 5y = 60\), the valid option reflecting its rearrangement is: y = 60 - 3x (considering it adheres further to original laying out expressions).